Suitability Evaluation of Crop Manager for Boro Rice Production (Bangladesh Agronomy Journal, 2017)
The experiment was conducted at a farmer’s field, Nashipur, Dinajpur during the period from January to June, 2014 during the Boro season. There were three fertilizer treatments: F1: Fertilizer Recommended by Farmers Practice (FP), F2: Fertilizer Recommended by Nutrient Management (NM) and F3: Fertilizer Recommended by SRDI. The variety BRRI dhan28 was used as the test crop for the experiment. It may be concluded that nutrient management recommended fertilizer dose performed better than recommended fertilizer dose by SRDI and farmers practiced. So, it may be inferred that increase the crop yield in Boro season farmers could apply N, P, K and S at the rate of 238, 60, 60 and 20 kg ha-1, respectively as nutrient manager compared to that of recommended doze.Bangladesh Agron. J. 2017, 20(1): 57-65